2013
DOI: 10.5539/ass.v10n2p209
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Long-Term Orientation and Service Recovery on the Relationships between Trust, Bonding, Customer Satisfaction and Customer Loyalty: The Case of Nigerian Retail Banks

Abstract: In spite of consolidation of Nigerian retail banks, the industry is still embattled by customer complaints, lost of customer confidence and loyalty erosion. Extant literature has amply reported the associations between relational dynamics of trust, bonding, customer satisfaction and customer loyalty. However, these reports are contradictory and thus, inconclusive. Meanwhile, literature has argued extensively on the influence of cultural values on customer decision making and buying behaviour. Yet, very little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 89 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…There has been a rising need to enhance the bank-customer interface in terms of service delivery. The ultimate goal is to ensure that customers are satisfied with the bankssatisfaction with which researchers (Abubakar, Mokhtar, & Abdullattef, 2013;Akgam & Murugiah, 2013;Erjavec et al, 2016) have shown to increase the likelihood of bank customer loyalty and retention. Lee and Lee (2013) argued that customer's satisfaction is one of the most critical issues facing contemporary managers of service industries.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a rising need to enhance the bank-customer interface in terms of service delivery. The ultimate goal is to ensure that customers are satisfied with the bankssatisfaction with which researchers (Abubakar, Mokhtar, & Abdullattef, 2013;Akgam & Murugiah, 2013;Erjavec et al, 2016) have shown to increase the likelihood of bank customer loyalty and retention. Lee and Lee (2013) argued that customer's satisfaction is one of the most critical issues facing contemporary managers of service industries.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has shown the moderating role of individual cultural values on green consumer behaviour, e.g., the more individualistic a consumer is, the more likely they are to develop good practices (Lu et al, 2015). Similarly, the moderating effect of long-term orientation in building loyalty to the restaurant has been studied , and also in other domains such as higher education (Abubakar & Mokhtar, 2015) or banking (Abubakar et al, 2013). Similarly, individual cultural values have a clear determinant role (cause or antecedent), empirically demonstrated in areas such as education, in an attempt to understand how it affects the likelihood of bullying or being a victim of bullying (Georgiu et al, 2018), and also in consumer behaviour (Czarnecka et al, 2020).…”
Section: Introductionmentioning
confidence: 99%